SWOT analysis of rice processing industry in Kano State, Nigeria: An empirical review (Agriculture, Food, and Natural Resources Journal, 2025)
The rice processing industry in Kano State, Nigeria, plays a pivotal role in the country's agricultural economy, contributing to food security and employment. This study aims to assess the strengths, weaknesses, opportunities, and threats within Kano's rice processing sector. A systematic review was adopted with the aid of a strength, weaknesses, opportunities, and threats (SWOT) analysis to evaluate the secondary information reviewed about rice value chain activities in Kano State, especially on rice processing industry-related studies. Results of the evaluation reveal the high profitability, availability of raw materials, and established irrigation systems as the strengths of the processing industries in the state. Weaknesses reported were low mechanization, high input costs, and poor infrastructure. Opportunities for growth lie in modernization, mechanization, and government support, while threats such as fluctuating input costs, competition with imported rice, and inconsistent government policies hinder the industry's potential. It is therefore concluded that the rice processing industry in Kano shows great potential for growth and profitability, but significant challenges need to be addressed. Investments in mechanization, infrastructure improvements, and access to credit are essential to overcoming the weaknesses and mitigating the threats facing the industry and are hence recommended.
Keywords: Mechanization; Processing; Profitability rice; SWOT